Радиоиммунотерапия в лечении злокачественных образований - Чернов В. И. Владимир Иванович; Брагина О. Д. Ольга Дмитриевна; Синилкин И. Г. Иван Геннадьевич; Медведева А. А. Анна Александровна; Зельчан Р. В. Роман Владимирович (Обзоры, 2015)
Заглавие с экрана